Centrifugally manufactured hollow concrete‐filled steel tubular columns - Artiomas Kuranovas; Audronis Kazimieras Kvedaras (Journal of Civil Engineering and Management, 2007)
Hollow concrete‐filled steel tubular elements (H‐CFSTs) represent a type of composite steel‐concrete elements. These elements are usually produced by spinning. During this process wet concrete mix in the steel tube is displaced and compacted by centrifugal force and the concrete core so formed achieves better physical and mechanical properties in comparison with other compaction methods. These improvements are related to concrete density, Young's modulus, Poisson’ s ratio, compressive strength, deformability as well as to a more uniform distribution of fine and coarse aggregates and binding particles along the thickness of the hollow concrete core formed by multi‐layering centrifugation process. The peculiarities of the spinning process, recommendations for proportioning the components for the specimens manufacture, spinning time needed for displacement and compaction of concrete mix, preparation of specimens for testing and testing methods used are presented in this paper.